Komparasi Pemikiran Al-Maududi dan Motesquieu tentang State Institute Relations - Moch. Misbahul (Asy-Syari’ah : Jurnal Hukum Islam, 2016)
The principle of separation of powers which is the basic concept of the relationship between state institutions is one attempt to limit the power of rulers. Montesquieu thought about this concept then used as the basis of the governance system by most countries of the world. Opt for this concept by some Muslim countries and the rapid establishment of state discourse on Islam gave birth to fundamental questions about how the concept of the relationship between state agencies when applied in Islamic countries and how Islam speak of the relationship between state institutions. And the only Muslim figures most representative and discuss the issues detailed in the relationship between state institutions within the framework of Islam are a`lâ Abul al-Maududi. From here interesting to study more deeply by a comparative study of how thought Montesquieu and al-Mawdudi on the relationship between state institutions.